Decorative Coatings of Crystallite Type on Metallic and Non-metallic Surfaces - Satayev1, M.S.; T. Koshkarbayeva1, Sh.; Tukibayeva2, A.S.; Zh. Tuleshova3, E. (Asian Journal of Chemistry, 2013)
The results of decorative coatings of ‘crystallite’ type on metallic and non-metallic surfaces are presented in this work. We propose the low-temperature chemical method that allows receiving the “crystallite” pattern with a preliminary assessment of decorative coating quality on all, including non-metallic materials. For this, at first a product is dipped for a few seconds into the saturated solution of copper salt at the temperature of 80-90 ºC for metals and 60 ºC for polymeric materials. At drying the product on air “crystallite” type patterns are formed onto its surface. If poor quality pattern is received, then it is easily washed off with water, thereupon repeating previous operations the qualitative patterns can be obtained. To fix the received in such way patterns of the product they are treated by gas, containing phosphine.